Epigenetic mechanisms and endocannabinoid signalling. (11th February 2013) - D'Addario, Claudio; Di Francesco, Andrea; Pucci, Mariangela; Finazzi Agrò, Alessandro; Maccarrone, Mauro
<x xml:space="preserve">Abstract</x> The endocannabinoid system, composed of endogenous lipids, their target receptors and metabolic enzymes, has been implicated in multiple biological functions in health and disease, both in the central nervous system and in peripheral organs. Despite the exponential growth of experimental evidence on the key role of endocannabinoid signalling in basic cellular processes, and on its potential exploitation for therapeutic interventions, much remains to be clarified about the respective regulatory mechanisms. Epigenetics refers to a set of post‐translational modifications that regulate gene expression without causing variation in DNA sequence, endowed with a major impact on signal transduction pathways. The epigenetic machinery includes DNA methylation, histone modifications, nucleosome positioning and non‐coding RNAs. Due to the reversibility of epigenetic changes, an emerging field of interest is the possibility of an 'epigenetic therapy' that could possibly be applied also to endocannabinoids. Here, we review current knowledge of epigenetic regulation of endocannabinoid system components under both physiological and pathological conditions, as well as the epigenetic changes induced by endocannabinoid signalling.